Study the Silica Content of Paddy Husks from Different Varieties of Paddy Cultivated in North Western Province, Sri Lanka - Jayathilake, S.M.C.Y.; Manoranjan, T. (University of Jaffna, 2022)
Rice husk is one of the main agricultural waste available in Sri Lanka. They are the outer covering of rice grains. Once the paddy is separated from rice grain, the husk is removed from rest of the grain. This study show depending on rice husk variety moisture content, average bulk density, amount of precipitated silica varies. Further EDX analysis show depending on variety percentage of Oxygen, Silicon and other contaminants are varied. Eight different rice husk varieties available in North Western Province is studied in this research. Moisture Content (MC), average bulk density and silica content in each variety were initially calculated. Moisture content varies between 10.42% to 12.84%. Average bulk density varies between 214.42 𝑘𝑔 𝑚−3 to 268.57 𝑘𝑔 𝑚−3 . Highest amount of silica was obtained as 98.2% from Murugakanayan rice variety. Lowest amount of silica was obtained as 74% from BG 360 rice variety. A typical XRD, SEM patterns and EDX was done to silica samples obtained from rice husk ash. Amorphous nature of the obtained silica was confirmed from XRD spectra. There is a broad peak with maximum intensity at 2Ө = 22 ͦin XRD spectra. SEM images have shown that these silica particles were aggregated as irregular rod shape clusters. EDX images confirm high amount of sample weight contain silicon and oxygen. Yet very less amount of sodium is available in the sample.
Keywords: Rice Husk; Rice Husk Ash; Silica; Extraction